PERAN KEPUASAN KONSUMEN MEMEDIASI PENGARUH MARKETING MIX TERHADAP NIAT BELI ULANG PRODUK H&M - Budiarto, Kevin Anggoro; Sukawati, Tjokorda Gde Raka (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.13.NO.04.TAHUN.2024DO - 10.24843/EEB.2024.v13.i04.p08, 2024)
Having stores in various shopping centers such as malls is an expansion of the H&M company's line of business. The products offered vary from t-shirts, shirts, shorts and long pants, hats, suits and other attributes. This phenomenon is the reason for knowing what strategies are implemented by H&M companies. The company's way to continue to compete is to implement a consistent marketing mix strategy. Making consumers feel satisfied to repurchase the same product in the future or also known as creating repeat purchase intentions. This study aims to analyze the role of consumer satisfaction in mediating the influence of the marketing mix on the intention to repurchase H&M products in the city of Denpasar. The results showed that the Marketing Mix had a significant positive effect on repurchase intentions, the Marketing Mix had a significant positive effect on Consumer Satisfaction, Consumer Satisfaction had a significant positive effect on repurchase intentions, Consumer Satisfaction mediated the influence of the Marketing Mix on repurchase intentions. The research is expected to be used later by H&M as a consideration in formulating marketing policies related to the marketing mix, consumer satisfaction so as to increase the intention to repurchase H&M products in Denpasar City.